Bundle sheath suberisation is required for C4 photosynthesis in a Setaria viridis mutant - Danila, Florence R.; Thakur, Vivek; Chatterjee, Jolly; Bala, Soumi; Coe, Robert A.; Acebron, Kelvin; Furbank, Robert T.; von Caemmerer, Susanne; Quick, William Paul (Springer, 2021)
C4 photosynthesis provides an effective solution for overcoming the catalytic inefficiency of Rubisco. The pathway is characterised by a biochemical CO2 concentrating mechanism that operates across mesophyll and bundle sheath (BS) cells and relies on a gas tight BS compartment. A screen of a mutant population of Setaria viridis, an NADP-malic enzyme type C4 monocot, generated using N-nitroso-N-methylurea identified a mutant with an amino acid change in the gene coding region of the ABCG transporter, a step in the suberin synthesis pathway. Here, Nile red staining, TEM, and GC/MS confirmed the alteration in suberin deposition in the BS cell wall of the mutant. We show that this has disrupted the suberin lamellae of BS cell wall and increased BS conductance to CO2 diffusion more than two-fold in the mutant. Consequently, BS CO2 partial pressure is reduced and CO2 assimilation was impaired in the mutant. Our findings provide experimental evidence that a functional suberin lamellae is an essential anatomical feature for efficient C4 photosynthesis in NADP-ME plants like S. viridis and have implications for engineering strategies to ensure future food security.